The influence of thumb-sucking habit towards anterior open bite on Javanese girls aged 6-7 years-old in Ngaglik District, Sleman, Yogyakarta - Risa Miyarsih; Iwa Sutardjo; Al-Supartinah Al-Supartinah (DiscoverSys Inc., 2020)
Objective:Â Thumb sucking is one of the factors that can influence dentomaxillofacial changes. It is caused by several factors, including the child's inability to respond to external factors. The aim of this study was to determine the influence of thumb sucking towards dentomaxillofacial changes.Material and Methods:Â The study was conducted with cross-sectional approach. The samples were Javanese girls aged 6-7 years who attended elementary school in Ngaglik district, Sleman, Yogyakarta. Samples were selected by selective random sampling, in which 22 children had thumb-sucking and 22 children without thumb-sucking as control group. Dental impressions were taken to measure overjet and overbite. The statistic test used in this study was Chi-Square test.Result: Thumb-sucking has significant influence to dentomaxillofacial changes (X2=10.47; p<0.001).Conclusion: Thumb-sucking has influence on dentomaxillofacial changes on Javanese girls aged 6-7 year-old in Ngaglik district, Sleman, Yogyakarta.